Estimation of salivary IL-6 and calprotectin in patients with ulcerative colitis - Fadhel A. Abdullah; Maha A. Mahmood (مجلة كلية الطب)
Inflammatory bowel disease (IBD) is chronic inflammation of the gastrointestinal tract (GIT) it includes two-condition Crohn’s disease (CD) and ulcerative colitis (UC) the prolonged inflammation may cause invasion of the multiple layers of the intestinal walls result in GIT damage. The current study was carried out in Baghdad teaching hospital and gastroenterology hospital from November 2021 to May 2022.  In order to show if the diagnostic marker of IBD which are IL6& calprotectin are rises in saliva as in sera and if there are significant differences in the levels of those markers between UC patients and healthy control subjects.